Exploring Covid-19 Research in the Built Environment Literature: A Bibliometric Analysis - Evren ÜLKERYILDIZ (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The disaster of “Covid-19 pandemic” which has been introducing various radical changes on the lifestyle of people such as (1) the usage of urban spaces, (2) spatial problems, (3) the transformation of shared spaces and (4) working practices. These radical changes have been receiving an overwhelming interest from scholars from various disciplines since SARS-CoV-2 corona (i.e., Covid 19) virus set a global pandemic. As a result of this overwhelming interest, a rich but a fragment literature prevails on the radical changes caused by Covid 19 pandemic in built environment studies. The research presented herein explores this rich but fragmented literature on the effects of Covid-19 pandemic by adopting a systematic research design strategy namely bibliometric analysis.  It is also discovered that the spatial reorganization response of countries to Covid 19 pandemic to varies from country to country mainly due to the regional characteristics of the countries.